2022
DOI: 10.1186/s13568-022-01486-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the initial pH on the anaerobic digestion process of dairy cattle manure

Abstract: Anaerobic digestion (AD) has recently been studied to obtain products of greater interest than biogas, such as volatile fatty acids (VFAs) and phytoregulators. The effect of the initial pH of cow manure and the fermentation time of the AD on the microbial composition, VFAs, indole-3-acetic acid (IAA) and gibberellic acid (GA3) production was evaluated. The cow manure (7% solids) was adjusted to initial pH values of 5.5, 6.5, 7.5, and 8.5, and the AD products were analyzed every four days until day 20. The init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…At pH less than 8, the SHAP values of biogas production were consistently negative, which affected biogas production. In the wet anaerobic digestion of cow manure, the VFA values were 653.3, 609.26, 836.5, and 1150.71 mg/L at pH 5.5, 6.5, 7.5, and 8.5, respectively, and VFA is an intermediate product of AD . VFA accumulation leads to acid inhibition, decreases anaerobic stability, and reduces biogas production .…”
Section: Resultsmentioning
confidence: 99%
“…At pH less than 8, the SHAP values of biogas production were consistently negative, which affected biogas production. In the wet anaerobic digestion of cow manure, the VFA values were 653.3, 609.26, 836.5, and 1150.71 mg/L at pH 5.5, 6.5, 7.5, and 8.5, respectively, and VFA is an intermediate product of AD . VFA accumulation leads to acid inhibition, decreases anaerobic stability, and reduces biogas production .…”
Section: Resultsmentioning
confidence: 99%
“…Metagenome analysis of microbiota from both HRFI and LRFI groups revealed that, at the phylum level, Bacteroidetes and Firmicutes were the most abundant microbiota in the rumen and feces, consistent with previous studies [ 38 , 39 , 40 ], and the abundance of Bacteroidetes in the rumen was higher in the LRFI group (23.1%) than in the HRFI group (10.1%). Studies have shown that Bacteroidete , Firmicutes and Prevotella can decompose polysaccharides that cannot be digested by the host in the intestinal tract, promoting the digestion and absorption of nutrients which provide energy for the host [ 41 , 42 , 43 ]; these bacteria may have an impact on host feed efficiency by affecting the volatile fatty acid concentration [ 44 ]. The main products of Bacteroidete are phosphobutyryltransferase and butyrate kinase [ 45 ], which promote the fermentation of resistant starch, indigestible oligosaccharides, and their derivatives in the rumen for energy supply, which is conducive to improving feed utilization in ruminants [ 46 ], thereby reducing feed costs.…”
Section: Discussionmentioning
confidence: 99%
“…At pH 8.5, the most VFAs were produced, and the order of generation of the acids was butyric > acetic > propionic. On days 20 and 4, respectively, the highest synthesis of indole-3-acetic acid and gibberellic acid occurred at initial pH values of 6.5 and 5.5 [38].…”
Section: Operating Phmentioning
confidence: 97%